Studi Populasi Serangga Sebagai Upaya Konservasi Biodiversitas Sungai Oyo, di Desa Wisata Bleberan Gunung Kidul - Eka Sulistiyowati (Jurnal Biologi Universitas Andalas, 2015)
Bleberan Village has ecotourism potential in terms of insects biodiversity. Moreover, this village has some beautiful tourism objects, such as Sri Gethuk waterfall and Rancang Kencono cave. In the other hand, biodiversity in this village is yet to be explored, hence this research aims at studying insects biodiversity, especially of  three orders: Orthoptera, Lepidoptera and Odonata. The final objective of this reseach is to provide information for studying and conserving biodiversity in this ecotourism region. The observation was conducted in 10 stations in both Kedung Poh (1st location) and Oyo River (2nd location ). Several ecological parameters were calculated such as density, diversity index, and distribution. In addition, enviromental parameters were also measured, i.e temperature, humidity, and light intesity. This research found 17 species of each order, with the highest number of individuals was observed in the member of Orthoptera, especially withPhlaeoba fumosa; 381 individuals (1st location 1) and  445 individuals (2nd location). In the order of Lepidoptera, species Catopsilia pomonahad the highest number of individuals, there were 31 and 46  individuals in 1st location and 2nd location, respectively. The latter is Odonata, had Orthetrum sabinawhich dominated the number with 252 individuals in 1st location and 188 individuals in 2nd location. This research also revealed that diversity index was varied between 0.79 and 0.99, with all orders were distributed in a clumped pattern. All the environmental factors had been observed and did not show any abnormality, therefore insects couldbe alive normally.